Micro-progettazione: pratiche a confronto. PROPIT, EAS, Flipped Classroom - Rossi, Pier Giuseppe (Traiettorie inclusive - Open Access, 2016)
"Micro-progettazione" ("micro-planning") are the processes carried out by the teacher to prepare the day after work session. Three models are analyzed and compared in the book: Propit, EAS and Flipped Classroom. Although each one has its own features, all of these models share the attention to micro-planning, the focusing on action and the interest in promoting an active and conscious attitude of the students.